Characterization of the sex determining region and development of a molecular sex identification method in a Salangid fish - Hao Yang; Yu-Long Li; Teng-Fei Xing; Jin-Xian Liu (BMC Genomics)
Abstract Background The short-snout icefish, Neosalanx brevirostris, a member of the Salangidae family, is an economically important fishery species in China. Understanding the mechanisms underlying sex determination in this species has crucial implications for conservation, ecology and evolution. Meanwhile, there is a shortage of rapid and cost-effective genetic methods for sex identification, which poses challenges in identifying the sex of immature individuals in sex determination mechanism studies and aquaculture breeding applications. Results Based on whole genome resequencing data, sex-specific loci and regions were found to be concentrated in a region on chromosome 2. All sex-specific loci exhibited excess heterozygosity in females and complete homozygosity in males. This sex determining region contains seven genes, including cytochrome P450 aromatase CYP19B, which is involved in steroidogenesis and is associated with 24 sex-specific loci and two W-deletions. A haploid female-specific sequence was identified as paralogous to a diploid sequence with a significant length difference, making it suitable for rapid and cost-effective genetic sex identification by traditional PCR and agarose gel electrophoresis, which were further validated in 24 females and 24 males with known phenotypic sexes. Conclusions Our results confirm that N. brevirostris exhibits a female heterogametic sex determination system (ZZ/ZW), with chromosome 2 identified as the putative sex chromosome containing a relatively small sex determining region (~ 48 Kb). The gene CYP19B is proposed as a candidate sex determining gene. Moreover, the development of PCR based method enables genetic sex identification at any developmental stage, thereby facilitating further studies on sex determination mechanisms and advancing aquaculture breeding applications for this species.